The Impact of Chinese Capitalist Business on Indonesia’s Economic Policy and Leadership - muhammad Sakur (Journal of Research in Social Science and Humanities, 2025)
This study examines the roots of Chinese capitalist business in Indonesia, which has expanded significantly over the past two decades through increased foreign direct investment (FDI) and bilateral trade. It highlights the historical, economic, and political factors shaping this dynamic, while analyzing the Indonesian government's role in managing the influx of Chinese investment using a qualitative-descriptive approach. The findings indicate that China’s economic involvement in Indonesia has deep historical roots, dating back to the colonial era, continuing through the post-independence period, and intensifying under China’s "Go Global" policy. Major infrastructure projects such as the Jakarta–Bandung High-Speed Railway illustrate Beijing’s broader geopolitical strategy. However, various challenges and controversies have emerged, particularly concerning environmental impacts, China's growing economic dominance, and Indonesia’s increasing dependency. These issues have sparked public debate and raised questions about the long-term sustainability of such economic ties. In response, the Indonesian government has taken measures to address these concerns by implementing stricter regulations, diversifying sources of foreign investment, and strengthening domestic capacity in key sectors. These efforts aim to ensure long-term benefits while safeguarding national economic sovereignty. This study offers valuable insights for policymakers, scholars, and the broader public on how to manage Indonesia’s economic relationship with China more strategically and sustainably, emphasizing the importance of balanced engagement and informed governance in an increasingly interconnected global economy.